2019
DOI: 10.21203/rs.2.12114/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Qualitative Evaluation of a Community Health Representative Program on Patient Experiences in Navajo Nation

Abstract: Background:Community Health Representatives (CHRs) overcome health disparities in Native communities by delivering home care, health education, and community health promotion. The Navajo CHR Program partners with the non-profit Community Outreach and Patient Empowerment (COPE), to provide home-based outreach to Navajo clients living with diabetes. COPE has created an intervention (COPE intervention) focusing on multiple levels of improved care including trainings for CHRs on Motivational Interviewing and provi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…Pathways participants discussed how working with a CHW increased their awareness of and access to a variety of health and social services resources. Similar findings have emerged in evaluations of other CHW-led care coordination programs among diverse populations (Hudson et al, 2019;Lalla et al, 2020). Our findings support a growing body of evidence outlining the effectiveness of CHWs as a key component of care coordination service delivery within Pathways among a general adult population.…”
Section: Discussionsupporting
confidence: 85%
“…Pathways participants discussed how working with a CHW increased their awareness of and access to a variety of health and social services resources. Similar findings have emerged in evaluations of other CHW-led care coordination programs among diverse populations (Hudson et al, 2019;Lalla et al, 2020). Our findings support a growing body of evidence outlining the effectiveness of CHWs as a key component of care coordination service delivery within Pathways among a general adult population.…”
Section: Discussionsupporting
confidence: 85%
“…The finding that patients aged 64 or younger had a greater response to the intervention than patients aged 65 or older is particularly salient, in light of the fact that type 2 diabetes is affecting Navajo and other Native populations at increasingly younger ages (26). A systematic review of tailored integrated diabetes primary care interventions found the opposite, namely that younger people, compared with older people, had higher HbA 1c values in followup (25).…”
Section: Discussionmentioning
confidence: 99%
“…A tailored physical activity program supported by providers trained in MI techniques also fuelled sense of optimism for the future in people with mental health conditions [29]. Among patients with diabetes, combining information provision, MI techniques, and meaningful relationships led to improved sense of control [30], while others reported that it drove optimism [31]. Provision of information combined with MI techniques was also identified as two intervention components perceived as most beneficial in people receiving antiretroviral therapy [32].…”
Section: Key Findingsmentioning
confidence: 99%